Pengaruh Kualitas Pelayanan dan Penanganan Keluhan Pelanggan Terhadap Minat Kunjungan Ulang Pada Bolly Departement Store Dompu - irfan Irfan; Nurul Hayat; Hermansyah Hermansyah (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the influence of service quality and customer complaint handling systems on customers' intention to revisit Bolly Department Store in Dompu. The background of this research is based on the importance of effective service strategies in maintaining customer loyalty amid the increasingly competitive retail business environment. The research approach used is quantitative, employing a survey method. Primary data were collected through questionnaires distributed to customers who had previously shopped at Bolly Department Store. The data collection technique used purposive sampling based on specific criteria, resulting in 98 respondents. Data analysis was conducted using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with the assistance of SmartPLS version 4.0 software. The results of the study indicate that both service quality and customer complaint handling have a positive effect on customers’ intention to revisit Bolly Department Store in Dompu. These findings suggest that excellent service and the company’s responsiveness in handling complaints can create a pleasant shopping experience, enhance customer trust, and foster loyalty that leads to repeat visits.